The Hybrid Specialization Model: Navigating Bureaucratic Rigidity through GovTech Co-creation in Indonesia - Ajeng Amalia Andi; Dodie Tricahyono; Agus Salim Andi (Journal of Renewable Engineering, 2026)
This study investigates how GovTech firms navigate bureaucratic rigidity to accelerate digital maturity in Indonesian local government. It examines the evolution of client needs, the operationalization of collaborative governance, and the structural design of a "Hybrid Specialization Model" within the Electronic-Based Government System (SPBE) framework. Utilizing a qualitative single-case study of the partnership between PT 4nesia Digital Solution and Cirebon City, data were triangulated through semi-structured interviews, field observations, and longitudinal SPBE evaluation reports. Results indicate a shift from technical procurement toward institutional legitimacy, driven by compliance with national SPBE indicators. Success depends on facilitative leadership to bridge sectoral silos. The proposed Hybrid Specialization Model boosted the SPBE Index from 3.17 to 4.13, though a sustainability gap persists requiring the codification of digital workflows into local policy. This research provides empirical evidence for value co-creation and offers a strategic blueprint for shifting from transactional relations to institutionalized partnerships.